Investimento em estruturas reprodutivas em três espécies de Salviniaceae (Polipodiopsida), com tamanho corporal contrastantes - Basulto, Sofía Ignacia Ramos (2018)
Plants respond to environmental stress through phenotypic plasticity. Many comparative studies between phylogenetically close taxa show that phenotypic plasticity can vary considerably in the pattern and amount of variation displayed. The optimal allocation theory predicts that the pattern of resource allocation results from changes in the environment to optimize the capture of essential resources to survival, growth, and reproduction. In addition, biomass allocation may be limited by architectural constraints, which change with plant size. The main objective of this work was to analyze the biomass of reproductive structures of 3 species of the Salviniaceae family, with contrasting body size, to differentiate the strategies in the allocation of the resources of these three congeneric species to understand if the allocation changes simply with the size of the plant or it reflects a function in the life history of the plant. The results showed that S. oblongifolia the largest body size species invested more biomass in high cost reproductive structures (megasporangia) than in microsporangia. Thus, we can conclude that species with larger body sizes will invest more in high-cost reproductive structures such as megasporangia.